Personal Income Tax and Government Revenue: Evidence from Oyo State - Adejare, Adegbite, Tajudeen (International Journal of Social and Administrative Sciences, 2017)
The study examined the effect of Personal income tax on revenue generation in Oyo state. It also analyzed the significant components of Personal income tax on revenue generation in Oyo state. Data were obtained from approved budgets of the Oyo State government from 1990 to 2015. Pearson product moment correlation and multiple regressions were employed to analyze the relationship between the dependent variable (Revenue Generation in Oyo State) and independent variables (Pay As You Earn(PAYE), Capital Gain Tax, Road Tax, and Other Taxes ( Stamp duties, Betting and Gaming Taxes, Business Premises and registration levies, Development levies and Market fees)). Findings show that there is a positive significant effect of Pay As You Earn (PAYE) on Government Revenue in Oyo state (β = .1393567; p ≤ 0.05). All other variables have positive significant effect on Government Revenue in Oyo state with the exception of Capital gain tax which has negative effect on Government Revenue in Oyo state with the adjusted R2 @ 96.4%. In conclusion, Personal income tax impacted Government Revenue positively, strongly, significantly and statistically in Oyo State. It is now recommended that Oyo state government should look inward on how more internal revenue will be generated extensively in the state in order to achieve micro objectives of the government, and to eradicate the paucity of government revenue.